The burden of sepsis in critically ill human immunodeﬁciency virus-infected patients-a brief review - Moreira,José (2015)
Since the advent of highly active antiretroviral therapy in 1996, we have seen dramatic changes in morbi-mortality rates from human immunodeﬁciency virus-positive patients. If on the one hand, the immunologic preservation-associated with the use of current antiretroviral therapy markedly diminishes the incidence of opportunistic infections, on the other hand it extended life expectancy of human immunodeﬁciency virus-infected individuals similarly to the general population. However, the management of critically ill human immunodeﬁciency virus-infected patients remains challenging and troublesome for practicing clinician. Sepsis - a complex systemic inﬂammatory syndrome in response to infection - is the second leading cause of intensive care unit admission in both human immunodeﬁciency virus-infected and uninfected populations. Recent data have emerged describing a substantial burden of sepsis in the infected population, in addition, to a much poorer prognosis in this group. Many factors contribute to this outcome, including speciﬁc etiologies, patterns of inﬂammation, underlying immune dysregulation related to chronic human immunodeﬁciency virus infection and delays in prompt diagnosis and treatment. This brief review explores the impact of sepsis in the context of human immunodeﬁciency virus infection, and proposes future directions for better management and prevention of human immunodeﬁciency virus-associated sepsis.